Accuracy of endoscopic ultrasound with transabdominal ultrasound in the diagnosis of common bile duct stone in University of Malaya Medical Centre / Cheah Churn Choong - Cheah , Churn Choong (2017)
Introduction Choledocholithiasis is a very common condition worldwide and is associated with significant morbidity and mortality. Previously, the diagnosis of choledocholithiasis was made by transabdominal ultrasonography (TAS) followed by endoscopic retrograde cholangiopancreatography (ERCP) if suspicious of choledocholithiasis. Unfortunately, the sensitivity of TAS is low. On the other hand, ERCP carries a high risk of complications and should strictly be reserved only for therapeutic purposes. In the last two decades, endoscopic ultrasound (EUS) has been increasingly used in the diagnosis of suspected choledocholithiasis. Previous studies have shown EUS to be highly accurate compared to transabdominal ultrasound, but at the same time has a much lower complication rate than ERCP. Objective Primary Objectives: • To determine the sensitivity, specificity, positive predictive value, and negative predictive value of EUS in the diagnosis of CBD stones in University Malaya Medical Centre • To compare the accuracy of EUS vs T AS in patients (who have undergone both procedures) in the diagnosis of CBD stones. Secondary Objective: • To assess the positive and negative predictive values of EUS depending on the individual's probability for choledocholithiasis. • To identify the baseline demography of the patients with conftrrned choledocholithiasis and predactive factors for the diagnosis of choledocholithiasas. Methods This is a retrospective study where all patients with suspected choledocholithiasis who underwent both EUS and TAS from 2011 to 2016 were recruited. The baseline demography, symptoms, biochemistry, TAS finding and EUS findings were recorded. The final diagnosis of choledocholithiasis was made based on ERCP finding and clinical outcome following a minimum six-month follow up and subsequently the sensitivity, specificity, positive predictive value and negative predictive value for EUS and T AS were calculated. Results 192 patients were recruited. 93{48.4%) had choledocholithiasis. EUS has the sensitivity of 95.7% and 84.8% specificity; TAS has 41.9% sensitivity and 88.9% specificity. Conclusions Endoscopic ultrasonography (EUS) remains high accuracy for detecting choledocholithiasis compared to transabdominal ultrasonography (TAS). In our study, none of the predictors (Age, Ethnicity, Gender, Abdominal pain, Elevated GOT, ALP, AST, ALT, WBC and Amylase) were found to be associated with choledocholithiasis.